2020
DOI: 10.17843/rpmesp.2020.372.4518
|View full text |Cite
|
Sign up to set email alerts
|

Participación social, un factor a considerar en la evaluación clínica del adulto mayor: una revisión narrativa

Abstract: La participación social es definida como la integración de las personas a actividades de la comunidad en grupos sociales voluntarios u obligatorios, formales e informales, lo cual podría tener consecuencias en la salud de la población adulta mayor. Fue realizada una búsqueda en Pubmed, Scielo, Scopus y Google Scholar. Para esta revisión se analizaron 16 artículos que estudiaban el impacto de la participación social en adultos mayores, incluyendo un total de 73 698 096 individuos de Norteamérica, Asia, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
2
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 52 publications
0
2
0
3
Order By: Relevance
“…To date, previous studies have investigated social participation using survey data because there is no standard measurement tool for social participation. Social participation is defined as the involvement of people in community activities either voluntary or mandatory, or formal and informal social groups ( 9 ). Guo et al operationalized social participation as the four items that included visiting friends or family; attending religious services; participating in clubs, classes, or other organized activities; and going out for enjoyment ( 25 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To date, previous studies have investigated social participation using survey data because there is no standard measurement tool for social participation. Social participation is defined as the involvement of people in community activities either voluntary or mandatory, or formal and informal social groups ( 9 ). Guo et al operationalized social participation as the four items that included visiting friends or family; attending religious services; participating in clubs, classes, or other organized activities; and going out for enjoyment ( 25 ).…”
Section: Discussionmentioning
confidence: 99%
“…To date, studies have shown that dietary factors (less alcohol consumption and more tea consumption), sufficient sleep, and more social participation have key roles in preventing depression among older adults ( 5 , 8 ). Social participation is defined as the involvement of people in activities either voluntarily or mandatorily in formal or informal social groups ( 9 ). Social participation builds resilience owing to the social support received, and resilience is critical for maintaining independence and facilitating active aging ( 10 ).…”
Section: Introductionmentioning
confidence: 99%
“…Estos hallazgos son similares a los publicados por otros autores 17,18 . Estudios recientes en América Latina han observado que un buen nivel educacional y económico está altamente relacionado con mayor funcionalidad, salud mental, menor discapacidad y prevalencia de enfermedades y con un alto nivel de participación social principalmente en adultos mayores 17,19,20 . La Organización Mundial de la Salud por medio de la Clasificación Internacional de Discapacidad y Funcionalidad (CIF) describe una estrecha relación entre las funciones físicas con el nivel de autonomía y de participación en la comunidad 8 .…”
Section: Discussionunclassified
“…Diversos estudios han reportado efectos protectores de la participación social para la salud del adulto mayor, considerada como un estímulo para aumentar el nivel de actividad física y la capacidad de sociabilización (Sepúlveda-Loyola et al, 2020). Además, se agrega la importancia de permitirles que se impliquen en los procesos de toma de decisiones desde la propia familia y la comunidad.…”
Section: Introductionunclassified
“…Arlen Fernández Plasencia,Elianni de la Caridad González Carbó,Elizabeth Rodríguez Valdivia, población, debido a que la participación social es un estímulo que mantiene a la persona mayor vinculada con el medio y la comunidad. Al participar en reuniones, se mantiene conectado en el tiempo y el espacio, así también interactúa con otros, lo cual estimula los sistemas sensoriales, la autoestima, la afectividad y el apoyo emocional y psicológico (Sepúlveda-Loyola et al, 2020).…”
Section: Introductionunclassified